Experimental biomedical research: achievements and future aims - DONTA (Ι. ΔΟΝΤΑ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
An invaluable amount of knowledge and enormous progress in the advancement of human health, longevity and quality of life has been achieved by biomedical research throughout the ages. Most of the achievements were accomplished by research on animals and more recently, on laboratory animals. Progress in the production of drugs, vaccines, sera, antibiotics, surgical techniques and materials, diagnostic and therapeutic methods, and many more, was reached by their safety and efficacy testing on laboratory animals, prior to their application on humans. The achievements resulting from this research are applied both in humans and in animals. Experimental biomedical research is currently conducted in animal models of human diseases, invertebrates and with alternative methods to the use of animals. Its future aims are to solve existing and emerging health threats and to increase gene therapy, with the concomitant application of the three Rs principles of animal use - replacement, reduction and refinement.